The Influence of Soaking Duration of Artificial Chitosan from by Product Frozening Shrimp on the Effectiveness of Fresh Quality Tilapia (Oreochromis Niloticus) - Ayu Diana; Marnida Yusfiani; Anggi Anshori (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
One of the problems that often arise in the fisheries sector is to maintain quality. Chitosan as a natural preservative is an alternative because it is synthesized from shrimp shells and from invertebrate animal shells. Shrimp shell containing chemical compounds chitin and chitosan is a waste that is easily obtained and available in large quantities, which has not been utilized optimally, therefore it is necessary to utilize shrimp waste into chitosan as a preservation of freshness quality in tilapia. Realizing healthy food ingredients and types of preservation that are safe for the human body is the first step to improve a better quality of life. This study aims to determine the benefits of artificial chitosan as a preservative to improve the quality of freshness in tilapia (Oreochromis niloticus). The method in this research is an experimental method by preserving tilapia (Oreochromis niloticus) with different immersion times of artificial chitosan. The design carried out was a completely randomized non-factorial design. The observed parameters were the organoleptic test, the TVB test, and the test of the peroxide results from all tests showing that three hours of submersion was better than 1 and 2 hours of substation, all in relation to 7, 9 and 11 hours of observation. A seventh-hour observation is picking up no difference between 1, 2 and 3 hours of submersion.